Identification and functional analysis of hub genes involved in deoxynivalenol-induced enterotoxicity in porcine (Sus scrofa) - Jinhua He; Geng Zhao; Mingxia Chen; Ximing Ren; Peizhi Zhu; Zhizhong Liu; Jiayi Zhou; Hanwei Chen; Chuqiao Xiao; Xiang-Guang Li (Ecotoxicology and Environmental Safety)
Deoxynivalenol (DON) is a type of mycotoxin commonly found in food and animal feed. When consumed, it can have harmful effects on the intestine. The porcine digestive system is physiologically similar to that of humans, making pigs a suitable model for studying DON-induced enterotoxicity. However, the exact ways DON causes intestinal damage in pigs still need to be fully understood. To address this knowledge gap, this study aimed to identify hub genes associated with enterotoxicity caused by DON exposure. Transcriptomic datasets from porcine jejunal explants exposed to DON were extensively analyzed using bioinformatic techniques in this study. A total of 265 differentially expressed genes (DEGs) were identified, with 238 being up-regulated and 27 being down-regulated, indicating that exposure to DON tends to increase gene expression. Further analysis revealed that the up-regulated DEGs were enriched in tumor necrosis factor, nuclear factor kappa-B, mitogen-activated protein kinases, and Janus kinase/signal transducer and activator of transcription-related signaling pathways. In addition, Weighted gene co-expression network analysis was performed to identify highly co-expressed modules. Then, genes in the highest co-expressed module were intersected with the up-regulated DEGs to construct a Protein-Protein Interaction network, resulting in 237 overlapping genes. Subsequently, 6 hub genes (CXCR4, PTGS2, ICAM1, IL-1A, IL-1B, and IL-10) that played a central role in the response to DON were identified using cytohubba in conjunction with the Molecular Complex Detection. In summary, exposure to DON is more likely to result in increased rather than decreased gene expression. Six of the upregulated genes, which are involved in immunoregulation and inflammation, were identified as hub genes related to DON-induced enterotoxicity in pigs. This study provides new insights into the mechanisms underlying DON-induced enterotoxicity and could guide interventions for this condition.